CodeBuddy: A Programming Assignment Management System for Short-Form Exercises - Stephen R. Piccolo; Emme Tuft; P. J. Tatlow; Zach Eliason; Ashlie Stephenson (Journal of Open Research Software)
CodeBuddy is a software system for delivering computer-programming assignments to students. It is primarily used for short-form exercises, such as those delivered in introductory-programming courses and informal-learning settings. It provides a Web-based interface, the ability to execute code in a secure environment, support for custom testing logic, near-immediate feedback to students, and support for many programming languages. Other features include support for graphics-based programming exercises, pair programming, the ability for students to review the instructor’s solution after solving an exercise, and an intelligent tutor. Upon creating an account, each student is randomly assigned to an “A” or “B” cohort, thus enabling researchers to perform pedagogical research via online controlled experiments. These and other features offer opportunities for instructors to customize the learning experience, in diverse ways, for students learning to program.